Evaluation of contrast visual acuity in patients with retinitis pigmentosa - Oomachi K (Dove Medical Press, 2011)
Kazumi Oomachi1, Kazuha Ogata2, Takeshi Sugawara2, Akira Hagiwara2, Akira Hata1, Shuichi Yamamoto21Department of Public Health; 2Department of Ophthalmology, Chiba University Graduate School of Medicine, Chiba, JapanBackground: The purpose of this study was to determine visual acuity at different contrast levels under photopic and mesopic conditions in patients with retinitis pigmentosa.Methods: Sixty eyes of 31 normal controls, 92 eyes of 52 patients with retinitis pigmentosa without other ocular disorders (RP-1 group), and 20 eyes of 14 patients with retinitis pigmentosa with cataracts and without other ocular disorders (RP-2 group) were studied. Conventional visual acuity was measured using a conventional Landolt ring chart with 100% contrast and luminance of 150 cd/m2. All of the patients with retinitis pigmentosa had a decimal visual acuity better than 1.0. Contrast visual acuity was measured with the same Landolt ring chart with contrasts of 100% and 10% and under photopic (200 cd/m2) and mesopic (10 cd/m2) conditions. Decimal visual acuities were converted to logMAR units for the analyses.Results: The 100% contrast visual acuity and the 10% contrast visual acuity determined under both photopic and mesopic conditions were significantly poorer in both the RP-1 and RP-2 groups than in the controls. The differences between the conventional visual acuity and the 100% contrast visual acuity were significantly greater in the RP-1 and RP-2 groups than in the controls under both photopic and mesopic conditions. The differences between the 100% contrast visual acuity and the 10% contrast visual acuity were not significant among the three groups under photopic and mesopic conditions.Conclusion: Contrast visual acuities were greatly reduced in patients with retinitis pigmentosa with relatively well preserved conventional visual acuity, and the contrast visual acuity was largely influenced by ambient light levels in patients with retinitis pigmentosa. Although a longitudinal study for confirmation has to be performed, our findings indicate that contrast visual acuity is a better test to follow changes in visual function in patients with retinitis pigmentosa.Keywords: retinitis pigmentosa, contrast visual acuity, photopic vision, mesopic vision